THE EFFECT OF CONVECTION ON CORE-COLLAPSE SUPERNOVAE - Telman, Yerassyl (Nazarbayev University School of Sciences and Humanities, 2024)
Modern Astrophysics, and the study of Core-Collapse Supernovae in particular, require an intense computational power and convenient code for different machines. A portable versatile code IDEFIX is able to deal with these issues. This thesis demonstrates a simulation of Core-Collapse Supernova with stable shock using IDEFIX. The model has an outer accreting part and inner shock. The code provides an extensive possibilities to efficiently modify the model for specific needs. Throughout the work, we obtain standing accretion shock instability (SASI) with 3D simulations, as well as observe how an outer convective shell with velocity perturbations affect the shock and SASI for different perturbation profiles. Additionally, we provide a way of analyzing those accreting perturbations which hints towards the future research of this topic.
Keywords: Core-Collapse Supernovae; Type of access: Open Access